The Effect of Leverage, Profitability, Asset Composition, Liquidity, Capital Turnover, and Cash Flow on Fraudulent Financial Reporting - Robiansyah, Anton; Suranta, Eddy; Midiastuty, Pratana Puspa; Fachruzzaman, Fachruzzaman (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aimed to see if financial ratios and cash flow patterns affect fraudulent financial reporting. The Beneish M-Score and Altman Z-Score models are used in this study to classify companies that commit fraudulent financial reporting and those that do not commit fraudulent financial reporting. According to the findings of this study, leverage ratio, profitability, asset composition, liquidity, capital turnover, and cash flow pattern types 2,3,4, and 6 all impact fraudulent financial reporting. This study's implications include theoretical knowledge from signaling theory relevant to corporations' fraudulent financial reporting. These findings can be used as information material for investors to see the criteria for companies that do fraudulent financial reporting using financial ratios and cash flow patterns from operating, investing, and funding activities so that they can be considered in making investment decisions for investors and become a reference in further research